Outcomes of Surgical Treatment of Vaughan-Jackson Syndrome - Mcintyre, Joshua L.; Stirling, Paul H.C.; Mceachan, Jane (Journal of Wrist Surgery, 2024)
Background Vaughan-Jackson syndrome (VJS) is the attritional rupture of the extensor tendons secondary to arthritis or inflammation affecting the distal radioulnar joint. The surgical outcomes following Darrach's procedure and tendon transfers are not well described. The primary aim of this study was to report patient-reported functional outcome measures after surgery for VJS. Secondary aims were to report health-related quality-of-life scores, patient satisfaction, and complicationsMethods A single-center retrospective study was performed to identify patients who underwent surgical intervention for the management of VJS. Patient-reported outcomes were measured using the Patient-Rated Wrist and Hand Evaluation (PRWHE), Quick version of the Disability of the Arm, Shoulder, and Hand (QuickDASH), EuroQoL 5-dimensions 5-Likert (EQ-5D-5L), and calculation of the Net Promoter Score (NPS).Results We report postoperative patient-reported functional outcome measures for 12 cases of VJS treated with distal ulna excision and extensor tendon transfer. The mean age was 69 years (range: 45–87 years; standard deviation [SD]: 14.1), and eight patients were females. Five patients had rheumatoid arthritis, and there was one case each of seronegative polyarthritis, ankylosing spondylitis, and CREST (calcinosis, Raynaud phenomenon, esophageal dysmotility, sclerodactyly, and telangiectasia.) syndrome; the rest of the patients had osteoarthritis. At a mean of 53 months of follow-up, the mean PRWHE score was 34.5 (SD: 17.9), the mean QuickDASH score was 28.2 (SD: 18.6), and the mean EQ-5D-5L score was 0.71 (SD: 0.203). Ten patients were satisfied and the NPS was 42. Postoperatively eight patients had pain scores reported as none or mild, three as moderate, and one as severe. Two patients required further operations, both undergoing total wrist arthrodesis.Conclusion Although a degree of functional deficit persists after Darrach's procedure and tendon transfer for treatment of VJS, there are also high levels of patient satisfaction, a good NPS, and a low rate of operative reintervention.Level IV evidence.
Keywords: Vaughan-Jackson; distal radioulnar joint; tendon rupture; tendon transfer